Production of Extracellular Laccase from Bacillus subtilis MTCC 2414 Using Agroresidues as a Potential Substrate - Narayanan P. Muthukumarasamy; Beenie Jackson; Antony Joseph Raj; Murugan Sevanan (Biochemistry Research International)
Laccases are the model enzymes for multicopper oxidases and participate in several applications such as bioremediation, biopulping, textile, and food industries. Laccase producing bacterium, Bacillus subtilis MTCC 2414, was subjected to optimization by conventional techniques and was partially purified using ammonium salt precipitation method. The agroresidue substrates used for higher yield of laccase were rice bran and wheat bran. Maximum production was achieved at temperature 30°C (270 ± 2.78 U/mL), pH 7.0 (345 ± 3.14 U/mL), and 96 h (267 ± 2.64 U/mL) of incubation. The carbon and nitrogen sources resulted in high enzyme yield at 3% sucrose (275 ± 3.11 U/mL) and 3% peptone (352.2 ± 4.32 U/mL) for rice bran and 3% sucrose (247.4 ± 3.51 U/mL) and 3% peptone (328 ± 3.33 U/mL) for wheat bran, respectively. The molecular weights of partially purified laccase were 52 kDa for rice bran and 55 kDa for wheat bran. The laccase exhibited optimal activity at 70°C (260.3 ± 6.15 U/mL), pH 9.0 (266 ± 4.02 U/mL), and metal ion CuSO4 (141.4 ± 6.64) was found to increase the production. This is the first report that delivers the higher yield of laccase produced from B. subtilis MTCC 2414 using agroresidues as a potential substrate.